Question
upstudy study bank question image url

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)

Ask by Mitchell Salinas. in Mexico
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Aquí están los resultados de las expresiones: 1. \( (x+2)^2 = x^2 + 4x + 4 \) 2. \( (x+2)(x+3) = x^2 + 5x + 6 \) 3. \( (x+1)(x-1) = x^2 - 1 \) 4. \( (x-1)^2 = x^2 - 2x + 1 \) 5. \( (n+3)(n+5) = n^2 + 8n + 15 \) 6. \( (m-3)(m+3) = m^2 - 9 \) 7. \( (a+b-1)(a+b+1) = (a+b)^2 - 1 \) 8. \( (1+b)^3 = 1 + 3b + 3b^2 + b^3 \) 9. \( (a^2+4)(a^2-4) = a^4 - 16 \) 10. \( (3ab-5x^2)^2 = 9a^2b^2 - 30abx^2 + 25x^4 \) 11. \( (ab+3)(3-ab) = 3ab - a^2b^2 + 9 \) 12. \( (1-4ax)^2 = 1 - 8ax + 16a^2x^2 \) 13. \( (2a+x)^3 = 8a^3 + 12a^2x + 6ax^2 + x^3 \) 14. \( (x^2-11)(x^2-2) = x^4 - 13x^2 + 22 \) 15. \( (x+y+1)(x-y-1) = x^2 + (y-1)x + (y-1) \) Continuando: 16. \( (1-a)(a+1) = -a^2 + 1 \) 17. \( (m-8)(m+12) = m^2 + 4m - 96 \) 18. \( (x^2-1)(x^2+3) = x^4 + 2x^2 - 3 \) 19. \( (x^3+6)(x^3-8) = x^6 - 2x^3 - 48 \) 20. \( (5x^3+6m^4)^2 = 25x^6 + 60x^3m^4 + 36m^8 \) 21. \( (x^4-2)(x^4+5) = x^8 + 3x^4 - 10 \) 22. \( (a^x+b^n)(a^x-b^n) = a^{2x} - b^{2n} \) 23. \( (x^{a+1}-8)(x^{a+1}+9) = x^{2(a+1)} + x^{a+1} - 72 \) 24. \( (a^2b^2+c^2)(a^2b^2-c^2) = a^4b^4 - c^4 \) 25. \( (x+5)(x-5)(x^2+1) = x^4 - 24x^2 - 25 \) 26. \( (a+1)(a-1)(a+2)(a-2) = a^4 - 5a^2 + 4 \) Finalmente: 27. \( (a^2+8)(a^2-7) = a^4 + a^2 - 56 \) Estos son los resultados de las expresiones proporcionadas.

Solution

A continuación, se presentan los resultados de las expresiones dadas, escritas por simple inspección: 1. \( (x+2)^{2} = x^{2} + 4x + 4 \) 2. \( (x+2)(x+3) = x^{2} + 5x + 6 \) 3. \( (x+1)(x-1) = x^{2} - 1 \) 4. \( (x-1)^{2} = x^{2} - 2x + 1 \) 5. \( (n+3)(n+5) = n^{2} + 8n + 15 \) 6. \( (m-3)(m+3) = m^{2} - 9 \) 7. \( (a+b-1)(a+b+1) = (a+b)^{2} - 1 \) 8. \( (1+b)^{3} = 1 + 3b + 3b^{2} + b^{3} \) 9. \( \left(a^{2}+4\right)\left(a^{2}-4\right) = a^{4} - 16 \) 10. \( \left(3ab-5x^{2}\right)^{2} = 9a^{2}b^{2} - 30abx^{2} + 25x^{4} \) 11. \( (a b+3)(3-a b) = 3ab - a^{2}b^{2} + 9 \) 12. \( (1-4ax)^{2} = 1 - 8ax + 16a^{2}x^{2} \) 13. \( (2a+x)^{3} = 8a^{3} + 12a^{2}x + 6ax^{2} + x^{3} \) 14. \( (x^{2}-11)(x^{2}-2) = x^{4} - 13x^{2} + 22 \) 15. \( (x+y+1)(x-y-1) = x^{2} + (y-1)x + (y-1) \) Continuando con las demás expresiones: 16. \( (1-a)(a+1) = -a^{2} + 1 \) 17. \( (m-8)(m+12) = m^{2} + 4m - 96 \) 18. \( \left(x^{2}-1\right)\left(x^{2}+3\right) = x^{4} + 2x^{2} - 3 \) 19. \( \left(x^{3}+6\right)\left(x^{3}-8\right) = x^{6} - 2x^{3} - 48 \) 20. \( (5x^{3}+6m^{4})^{2} = 25x^{6} + 60x^{3}m^{4} + 36m^{8} \) 21. \( (x^{4}-2)(x^{4}+5) = x^{8} + 3x^{4} - 10 \) 22. \( (a^{x}+b^{n})(a^{x}-b^{n}) = a^{2x} - b^{2n} \) 23. \( (x^{a+1}-8)(x^{a+1}+9) = x^{2(a+1)} + x^{a+1} - 72 \) 24. \( (a^{2}b^{2}+c^{2})(a^{2}b^{2}-c^{2}) = a^{4}b^{4} - c^{4} \) 25. \( (x+5)(x-5)(x^{2}+1) = (x^{2}-25)(x^{2}+1) = x^{4} - 24x^{2} - 25 \) 26. \( (a+1)(a-1)(a+2)(a-2) = (a^{2}-1)(a^{2}-4) = a^{4} - 5a^{2} + 4 \) Finalmente, para la expresión \( \left(a^{2}+8\right)\left(a^{2}-7\right) \): 27. \( \left(a^{2}+8\right)\left(a^{2}-7\right) = a^{4} + a^{2} - 56 \) Estos son los resultados de las expresiones dadas.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

¡Vamos a resolver algunas ecuaciones de manera divertida! Empezando con \( (x+2)^{2} \), el resultado es \( x^{2} + 4x + 4 \). ¡Es como tener dos amigos más que se suman en el camino! Por otro lado, para \( (x+y+1)(x-y-1) \), podemos aplicar la propiedad del distributivo y obtenemos \( x^{2} + (y-1)x + (-y-1) \). ¡Mira cómo se mezclan diferentes variables para crear algo nuevo!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy